Sistema de seguridad y su incidencia en transportación de vehículos pesados de la empresa Fish Transport S.A. - Andrade Álvarez, Karen Nelly (2022)
Logistics currently has an essential power in the transfer of goods between different destinations, taking into account that despite new technologies it continues to have a very important value in the logistics area, obtaining better management. although there is still room for improvement for some companies and institutions. One of the deficiencies that remains in this area is the visibility or control of the goods that are transported, which raises doubts if the transport of the goods arrives on time or arrives in good condition.........